Determining Factors That Influence Imports of Goods for Development in Indonesia: An Analytical Study - Muhammad Fitri Rahmadana (Outline Publisher, 2022)
Indonesia is recognized as a developing nation with a production industry that has yet to achieve sustainability to meet local demand. This is evidenced by Indonesia's reliance on external sources for consumer goods, raw and auxiliary materials, as well as capital goods. The country's importation activities stem largely from the inability of domestic products to compete with foreign counterparts, coupled with a societal inclination towards imported goods as a symbol of grandeur. The present study aims to conduct an analysis of the impact of gross domestic product (GDP), foreign exchange reserves, exchange rates, and inflation on imports within Indonesia during the 2000-2019 period. The analytical approach implemented in this research employs the Error Correction Model (ECM). The findings indicate that in the short term, GDP, foreign exchange reserves, and inflation have a positive and statistically significant impact on imports in Indonesia. In the long run, all the aforementioned variables exhibit a significant and meaningful influence on imports in Indonesia. In this regard, the provision of high-quality domestic production by government and producers is crucial for bolstering the domestic industry's development and rekindling local interest in domestic products.Indonesia is recognized as a developing nation with a production industry that has yet to achieve sustainability to meet local demand. This is evidenced by Indonesia's reliance on external sources for consumer goods, raw and auxiliary materials, as well as capital goods. The country's importation activities stem largely from the inability of domestic products to compete with foreign counterparts, coupled with a societal inclination towards imported goods as a symbol of grandeur. The present study aims to conduct an analysis of the impact of gross domestic product (GDP), foreign exchange reserves, exchange rates, and inflation on imports within Indonesia during the 2000-2019 period. The analytical approach implemented in this research employs the Error Correction Model (ECM). The findings indicate that in the short term, GDP, foreign exchange reserves, and inflation have a positive and statistically significant impact on imports in Indonesia. In the long run, all the aforementioned variables exhibit a significant and meaningful influence on imports in Indonesia. In this regard, the provision of high-quality domestic production by government and producers is crucial for bolstering the domestic industry's development and rekindling local interest in domestic products.